Most prevalent jobs of young master’s degree graduates by detailed field of study - Marc Frenette; Tomasz Handler (Economic and Social Reports)
Investing in a postsecondary education is an important decision in the lives of young people, because it may lead to significantly higher lifetime earnings (Frenette, 2019), which may vary substantially across different disciplines (Ostrovsky and Frenette, 2014). Beyond the monetary gains, the satisfaction derived from one’s day-to-day work activities may also matter in overall life satisfaction. To inform this issue, recent articles have examined the detailed occupations held by graduates of specific disciplines among bachelor’s degree graduates (Frenette and Handler, 2023) and among college or CEGEP certificate or diploma graduates (Frenette and Handler, 2024).